Model Pembelajaran Kooperatif Tipe Group Investigation dalam Meningkatkan Kemampuan Menerjemah Teks Bahasa Arab - Nur Inayatul Faizah; Fahrur Rosikh; Muhamad Arif Mustofa (Edu Journal Innovation in Learning and Education, 2023)
Learning methods have an important role in the success of learning. Among the learning methods that can be used in learning Arabic is the cooperative learning method. This study aims to determine the increase in student learning outcomes using the Group Investigation cooperative learning model in learning Arabic. the research method used was experimental research with the One group Prestest-Postest design. The research subjects were students of class XI IPS MA Hasyimiyah Tuban. The results showed that the Group Investigation learning model had an effect on increasing students' ability to translate Arabic texts. It can be seen from the results of the T-test that the results are 13.5 and d.b, namely N-1 = 37-1 = 36. Meanwhile, the T-test table using one group refers to a significant level of 0.05, namely 1.688 and 0.01, namely 2.434. The acceptance/rejection criteria for Hₒ and Hₐ are accepted if the results of the t test > t table are significant at 0.05 and 0.01. So it can be concluded that there is an effect of using the Group Investigation cooperative learning model in increasing the ability to translate Arabic texts.